The Effect of Leadership and Motivation on the Performance of UPT Central Bandung Regional Employees Bandung City Regional Revenue Agency (BAPENDA) - Anton Budi Santoso; Ridan Dwi Family (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the influence of leadership and motivation on the performance of UPT employees in the Central Bandung Region of the Regional Revenue Agency (Bapenda) of Bandung City. The method used in this research is a quantitative research method with a descriptive-verikative approach. Data collection techniques using a questionnaire with a saturated sampling technique is a sampling technique when all members of the population are used as samples, with a total sample of 15 respondents UPT Central Bandung Region BAPENDA Bandung City employee while the data source is primary data. Data analysis techniques using multiple linear regression include the coefficient of determination and hypothesis testing. From the results of the analysis either simultaneously or partially, it shows that Leadership and Motivation have a positive effect on the Performance of UPT Employees in the Central Bandung Region of the Regional Revenue Agency (Bapenda) of Bandung City.